PHOTOCATALYTIC DEGRADATION OF PHARMACEUTICAL WASTE USING ZNO/CUO THIN FILMS UNDER VISIBLE LIGHT - Dara Vann; Ravi Dara; Thiago Rocha; Siti Shofiah (Yayasan Adra Karima Hubbi, 2025)
The increasing presence of persistent pharmaceutical contaminants in water bodies poses a significant threat to environmental and human health, necessitating effective remediation technologies. This study aimed to develop and evaluate zinc oxide/copper oxide (ZnO/CuO) composite thin films as an efficient photocatalyst for degrading pharmaceutical waste under visible light. The ZnO/CuO thin films were synthesized via a sol-gel spin-coating method, and their photocatalytic activity was assessed using diclofenac as a model pollutant. The results demonstrated that the ZnO/CuO heterostructure exhibited enhanced visible light absorption and superior photocatalytic performance compared to pure ZnO. The composite films achieved over 90% degradation of diclofenac within 120 minutes, with the process following pseudo-first-order kinetics. The enhanced efficiency is attributed to effective charge separation at the ZnO/CuO interface. This research confirms that ZnO/CuO thin films are promising, reusable photocatalysts for the sustainable treatment of pharmaceutical-contaminated water.